Pelatihan Integrasi Penelitian dan Pengabdian Kepada Masyarakat (PKM) ke Mata Kuliah - Arif, Wiwin Pramita; Ali, Ahmad; Uyuni Taufiq, Ainul; Syamsul,; Sofyan, (KHIDMAH: Jurnal Pengabdian kepada Masyarakat, 2022)
Training on the integration of research and Community Service (Pkm) into courses aims to provide additional competencies to lecturers in preparing Semester Learning Plans (RPS). The subject of service was a Lecturer at the Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar as many as 8 participants with representatives from several study programs in the Faculty of Tarbiyah and Teacher Training UIN Alauddin. The data collection instrument uses a questionnaire that is distributed through a google form. Training on the integration of research and Community Service (Pkm) into this course is very in line with the needs of participants, namely in this case lecturers in preparing a Semester Learning Plan (RPS) and covering the entire content of the training theme. Training participants have an understanding in applying the integration of research and Community Service (Pkm) to courses and of course provide great benefits. This training is expected to be able to give birth to a guideline for the integration of research and PkM.